KUALITAS PELAYANAN IMUNISASI DI PUSAT KESEHATAN MASYARAKAT KINOVARO KECAMATAN KINOVARO KABUPATEN SIGI - Selviani, Selviani (Katalogis, 2016)
This study aims to determine the extent of the quality of Immunization Services in Public Health Centre of Kinovaro, Sigi Regency. This is a descriptive qualitative research. In this study, informants was determined by purposive sampling technique. The techniques of data collection in this study are Observation (observation), interviews, questionnaires and documentation. The results were analyzed by using the theory of Parasuraman et.al, while the concept used is Tangibles (physical evidence), Reliability, responsiveness, assurance (guarantees and certainty), Emphaty. The Results in this research was found that in terms of immunization services , the quality of existing services at the health center is not currently available Kinovaro optimally : (a) Services Kinovaro PHC terms of facilities (Tangibles) in immunization services still inadequate, where Kinovaro PHC can not meet the necessary of health personnel and facilities for community, especially in immunization activities; (b) Reliability of health workersin providing immunization services is not maximized, where Kinovaro PHC has given the simplicity of the immunization services procedure, but can not be carried out regularly, as well as health workers in immunization services have not been sufficiently trained to meet people's necessary for timely and keep standbye in all of work’s area; (c) Health worker’s responsiveness of immunization services at the Kinovaro PHC still not good, because health workers have not been able to provide a rapid response service to complaints receiver immunization services; (d) Security services (Assurance) given by health workers in immunization services at Kinovaro PHC, is still inadequate, because, health workers can not provide proper knowledge to society in their working area, and people do not get comfort when receive immunization by health personnel Kinovaro health center; (e) Being empathetic health workers in providing immunization services at health center Kinovaro, is still not good, where health officials Kinovaro PHC not competent to give less attention to community and understand the people’s necessary of receiving communities.